1981
DOI: 10.2337/diab.30.9.762
|View full text |Cite
|
Sign up to set email alerts
|

Regional Localization of Cerebral Edema Following Fluid and Insulin Therapy in Streptozotocin-Diabetic Rats

Abstract: To evaluate the location and early time course for development of cerebra edema following therapy for diabetes, streptozotocin-diabetic rats were subjected to constant i.v. infusion with saline and regular insulin. At the end of 1, 2, and 5 h of therapy, these rats were killed and tested for density of the cerebral cortex, subcortical white matter, caudate-putamen, thalamus, and medulla. Density data from treated animals were compared with those from control animals. From these data, change in brain tissue vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…High doses of insulin may also be a risk factor for cerebral oedema, as indicated by animal models [26,27] and supported by our observational studies. Finally, the dangers inherent in using large volumes of relatively dilute fluids have been highlighted by many studies [5,7,17].…”
Section: Discussionsupporting
confidence: 50%
“…High doses of insulin may also be a risk factor for cerebral oedema, as indicated by animal models [26,27] and supported by our observational studies. Finally, the dangers inherent in using large volumes of relatively dilute fluids have been highlighted by many studies [5,7,17].…”
Section: Discussionsupporting
confidence: 50%
“…42,43 Arief and Kleeman 44,45 have reported that insulin enhances the transport of electrolytes into the central nervous system, which may cause addition of osmotically active particles to brain tissue that could cause an uptake of osmotic water. In humans, John et al 46 suggested that the insulin-driven Na ϩ /H ϩ antiport might increase intracellular fluid by promoting Na ϩ influx into brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tornheim (17) extended the examination of the role of insulin in the induction of cerebral edema by treating streptozotocin‐induced diabetes in rats with varying intravenous fluid and insulin doses. Brain tissue density was not significantly altered by infusion of half normal saline over 5 h, but when insulin was added to the same fluid regimen, edema was significantly increased in all parts of the brain, particularly in the grey matter.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%